Working Mothers and "Machos Completos" - Gendered Modernity in Fertility Surveys in Colombia (1960s to 1970s) - Huhle, Teresa (Jahrbuch für Geschichte Lateinamerikas, 2023)
In 1960s and 1970s Colombia, physicians warned about demographic growth – or the “population explosion” – and addressed Colombian women and men as subjects who should come to understand the need to limit the size of their family. So-called fertility surveys were the key to understand existing attitudes with regard to the question. Furthermore, the doctors believed that the dissemination of their results would convince policy makers of the need to create family planning programs. Looking beyond this strategic moment, this article analyzes the gendered assumptions on women, men, sexuality and partnerships that informed the surveys and their results. In doing so, it places this medical-demographic knowledge production in the broader context of development and modernization debates in Colombia. Physicians became allies of feminist demands for women’s access to education and the job market, opened the discussion for sexual education, and joined ranks with the broad coalition that advocated for responsible parenthood. At the same time, the “médicos-demógrafos” planned the distribution of contraceptive methods without much regard for women’s health. In highlighting these tensions, the article contributes to the complex history of gender, medicine and health in the Americas.